Influence of Konjac oligo-glucomannan as cryoprotectant on physicochemical and structural properties of silver carp surimi during fluctuated frozen storage. (15th July 2022) - Walayat, Noman; Tang, Wei; Nawaz, Asad; Ding, Yuting; Liu, Jianhua; Lorenzo, Jose Manuel
Abstract: The aim of this study was to analyze the effect of Kanjoc oligo-glucomannan (KOG) on functional and structural changes in silver carp surimi during fluctuated (FLUC) frozen storage. During this study, KOG was prepared and added 1 and 3% in surimi and myofibrillar protein (MP) and compared with a positive control (PC) of sucrose and sorbitol mixture added samples. The results showed that the water holding capacity (WHC), textural and structural properties decreased during FLUC-I and FLUC-II, indicating that it could be due to protein denaturation induced by the formation of irregular crystallizations and recrystallization. Moreover, it was noted that the addition of KOG (3%) enhanced the stability of α-helix content (58–47%) during FLUC-I and (60–50%) during FLUC-II by inhibiting the hydrophobic residue exposure and change in aromatic amino acids. Meanwhile, KOG (3%) enhanced the textural properties by inhibiting the freeze induced protein denaturation. During FLUC frozen storage, the KOG (3%) was found to be a more effective concentration than conventional cryoprotectant mixture (PC). At industrial level, KOG (3%) could be used as a potential alternative to conventional cryoprotectants to attain prolonged commercial and economic values of silver carp. Highlights: Kanjoc oligo-saccharides (KOG) analyzed as cryoprotectant in silver carp surimi. KOG significantly reduced the protein changes during fluctuated frozen storage. Dense and compact gel was formed after incorporating KOG (3%). KOG (3%) improved the physicochemical and structural properties of surimi gel. KOG (3%) proved to be as a potential alternative to conventional cryoprotectants.